The Key Elements About How to Improve English Language Educators’ Teaching Competence through Continuous Professional Development (CPD) - LI, QIN; Mohammed, Lubna Ali (Journal of Ecohumanism, 2025)
This study aims to assess the impact of Continuing Professional Development (CPD) training on the teaching competence of English language educators at application-oriented universities in Henan, China. By employing a systematic literature review and bibliometric analysis, the study gathers and evaluates relevant data to understand the current state of CPD in English language instruction within this specific geographical and educational context. The research analyzes previous trends and their effects, identifying key areas for future refinement and targeted development. The study provides significant insights and practical implications for enhancing English language teaching competence through CPD in Henan and within the broader educational landscape of China. The findings indicate that recent publications from 2022 to 2024 have a limited citation impact, suggesting a lack of studies specifically addressing CPD’s role in English language training. Addressing this gap will help in the development of customized CPD programs for application-oriented universities, aligning with China’s strategic goals to improve English proficiency and promote international business and technological capabilities. The study also highlights that CPD research often draws insights from psychology and medical training, implying that a multidisciplinary approach can enhance the effectiveness of CPD for English language instruction. The relatively declining citation impact of Chinese educational research compared to European studies underscores the need for Chinese institutions to strengthen global collaborations and publish important findings in accessible journals to increase the global visibility and influence of their CPD advancements.